Force and torque reactions on a pitching flexible aerofoil. (25th April 2023) - Sanmiguel-Rojas, E.; Perona, J.L.; Fernandez-Feria, R.
Abstract: Abstract : Experimental measurements in a wind tunnel of the unsteady force and moment that a fluid exerts on flexible flapping aerofoils are not trivial because the forces and moments caused by the aerofoil's inertia and others structural tensions at the pivot axis have to be obtained separately and subtracted from the direct measurements with a force/torque sensor. Here we derive from the nonlinear beam equation general relations for the force and torque reactions at the leading edge of a pitching aerofoil in terms of the fluid force and moment on the aerofoil and its kinematics, involving geometric and structural parameters of the flexible aerofoil. These relations are validated by comparing high-resolution numerical simulations of the flow–structure interaction of a two-dimensional flexible aerofoil pitching about its leading edge with direct force and torque measurements in a wind tunnel.